Synthesis And Characterization Of Banana-Shaped Liquid Crystals - Lim, Lian Chin (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study is mainly to synthesize liquid crystals potential compounds derived from chalcone derivatives via esterification. New homologues series of banana-shaped liquid crystals (6a-6c) have been successfully synthesized via esterification based on modifications that have been made on model study (31). Initial steps were involving preparation of 4-alkoxybenzaldehydes (3a-3c) through etherification prior to chalcone bearing long alkyl chain (C10, C12, C14) (4a-4c) synthesis via Claisen-Schmidt reaction. Isophthaloyl dichloride was chosen as a starting material to react with alkylated hydroxyl chalcones (4a-4c) to form banana-shaped or bent-core liquid crystals properties. The compounds were characterized by IR, 1H NMR and 13C NMR spectroscopy.